The role of endophytic methane oxidizing bacteria in submerged Sphagnum in determining methane emissions of Northeastern Siberian tundra - Parmentier, F.J.W.; van Huissteden, J.; Kip, N.; Op den Camp, H.J.M.; Jetten, M.S.M.; Maximov, T.C.; Dolman, A.J. (Biogeosciences, 2011)
The role of the microbial processes governing methane emissions from tundra ecosystems is receiving increasing attention. Recently, cooperation between methanotrophic bacteria and submerged Sphagnum was shown to reduce methane emissions but also to supply CO